Bentuk Penyajian Tari Puti Bungo Api Sanggar Mandugo Ombak Di Kelurahan Ibuh, Kecamatan Payakumbuh Barat Kota Payakumbuh - Sucy Zulmaiza; Nerosti Nerosti (FBS Universitas Negeri Padang, 2022)
This study aims to analyze and describe the form of presentation of Puti Bungo Api Dance in the Mandugo Ombak Studio in Ibuh Village, Payakumbuh Barat District, and Payakumbuh City. This type of research is qualitative with a descriptive method. The object of research is Puti Bungo Api Dance, Mandugo Ombak Studio, Ibuh Village, West Payakumbuh District, Payakumbuh City with primary and secondary data types. Data collection techniques were carried out using library research, field observations, interviews, and documentation. All this data can be analyzed and accounted for. From the research conducted, it was found; that uniqueness; some conditions that must be owned by a dancer; the meaning of movement; floor pattern; the musical instrument used; makeup and costumes; property; the time and place of the performance.